Pengaruh Konsentrasi Silika dan laju Aliran Uap terhadap Kecepatan Scaling Pada Model Pipa Panas Bumi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
Scaling or deposition on the geothermal transmission pipes wall happen if the working steam which flow in it contents some minerals, like Silica and Carbonate. This research took steam as a model of geothermal fluid. The steam as fluid, be generated by a boiler. Three solution of silica be used, those were 57,1, 71,7 and 93,5 ppm. These concentrations based on the solubility of quartz at 133,5Â°C, and the working pressure i.e 2 atg, and three static pressure difference 0,4, 1,0 and 1,5 atg. The steam at certain condition was flowed in the specimen six hours. The scale thickness on the specimen wall had been measured by mean compared to the cuprum wire of 120 pm diameter. The deposition rates depend on the surface roughness, pressure differences, and minerals concentration in the solution and pH, can be approached by linear equations.